Thermal investigations on a CNC lathe fitted with a dynamically enhanced steel-reinforced epoxy granite bed - Ramana, Mula Venkata (Strojniški vestnik, 2023)
Polymer concrete or epoxy granite is becoming more popular for beds, bases, and other structures of precision machine tools, owing to its excellent damping characteristics. To realize the same static rigidity as that of the cast-iron structures, steel-reinforced epoxy granite (SREG) structures are being used. The vast differences in the thermal properties of steel and epoxy granite (EG) are likely to cause higher magnitudes of thermal error. This work aims to investigate the thermal behaviour of a computerized numerical control (CNC) lathe built with a novel dynamically enhanced SREG bed and compare its performance with the lathe with a cast iron bed. Experimental and numerical investigations have been carried out under cross-feed (CF) drive idle running conditions to determine the TCP deformation. The results reveal that the thermal error in the CNC lathe with SREG bed is 1.68 times that of the lathe with cast iron (CI) bed at 20 oC and 1.8 times at 40 oC environmental temperature variation chamber (ETVC) conditions. It could be identified that the heat generated in the CF is conducted to the steel guideways embedded in the SREG bed, but further heat transfer to the EG portion of the bed is impeded, and hence the heat accumulation that occurs in the guideways leads to higher magnitude of the thermal error. The experimentally validated numerical model is used to extend the investigations to study the effect of the idle running of the longitudinal feed drive (LF) and combined cross and longitudinal feed drives, on the thermal behaviour of the lathe.
Keywords: dušenje; epoksi granit; epoxy granite; jeklena ojačitev; polimerni beton; postelja stružnice; precision machine tools; precizni obdelovalni stroji; steel reinforcement; temperaturni raztezki; termična napaka; thermal error